need to see the steps so i can simplify need help
I am simplifying a fraction to lowest terms a^2 -4b^2/a+2b
I am simplifying a fraction to lowest terms a^2 -4b^2/a+2b
multiply and simplify (x^2+x-12/x-3)*(x^2-2x-3/x^2+5x+4)
What is the simplified form of the expression 3[14 ÷ (42 – 32) – 5]?
Simplified form of expression is it 1/6x or 11/6x
3n/n^2-49 - 2/3n+21
I need to see this simplifyed 7x+6=4x+27
try to simplify expressions.
Find the arc length of the curve defined by r(t)=(t, sqrt(6)/2*t^2, t^3), -1<=t<=1. r'(t)=<1, sqrt(6)t, 3t^2> sqrt(1+6t^2+9t^4) But how do I simplify this?
(–2 – c)(–1)
I need to simplify the follow expression
Need simplification for the maths problem
I have homework on multipling monomials and I need help on how to find the pattern to simplify process.
p1=[-3,2] p2=[5,6]
Find the value of 3x+5(x+9)-4x, when x=-5.
It's a subtraction fraction
please give me a correct answer.thanks
i cand figure this one out
i really dont know how to do it and i got mid terms this week
this problem is difucult. help me
Simplify (x^-5*(y^-6*z^1)^2)/(x^4*y^-1*z^-2) Write your answer with positive exponents only.